TV Channels, Self Control and Happiness - Christine Benesch; Bruno S. Frey; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2006)
In many countries, TV viewers have access to more and more TV channels. We study whether people can cope with this and watch the amount of TV they find optimal for themselves or whether they are prone to over-consumption. We find that heavy TV viewers do not benefit, but instead report lower life satisfaction when exposed to more TV channels. This finding runs counter to the standard economic prediction that a larger choice set does not make people worse off. It suggests that an identifiable group of persons experience a self-control problem when it comes to TV viewing.
Keywords: D12; D91; I31; J22; 330; Self-control; over-consumption; life satisfaction; experienced utility; TV viewing; Fernsehprogramm; Mediennutzung; Zufriedenheit; Europa